การเตรียมเซรามิกอะลูมินาความหนาแน่นสูงด้วยเทคนิคการพิมพ์ 3 มิติ - ภารดี เที่ยงธรรม (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
This study focuses on Preparation of Dense Sintered Alumina Ceramics by 3 D Printing Technique Fuse Deposition Modeling (FDM) type using PEG, PVA and PVB cobinders. The starting powder is alumina and the stearic acid is used as an additive. The mixing step of this study consists of 2 parts. The first part is dry mixing that mixed all raw materials with different ratio. The second part is wet mixing that used the ethylalcohol. Both powder and binders were formed the filaments through the extruder at 200 and 190 degree Celsius for using with 3 D printer FDM type and then formed the sample by 3 D printer FDM type. Double debinding steps were carried out using water leaching in the first part at 60 degree Celsius for 2.5 hours. The second part of debinding step was thermal debinding. Then the samples were sintered at 1650 degree Celsius for 2 hours. Characterisation of the filaments, the as-printed, the as-leached and the assintered including density, apparent porosity, water absorption, flexural strength and microstructure found that the alumina powder/binder ratio at 25:75 percent by volume is the best forming of the sample by 3 D printer FDM type, the wet mixing can be more homogenous than dry mixing, the side surface of the sample has the layers from FDM technique that each layer is not joint with another as well.